Censorship detected in IN (India) - Voidly (Voidly Global Censorship Index, 2025)
WARNING severity censorship detected in India. Data sourced from CensoredPlanet.
Censorship Incident ID: IN-2025-0004. Severity: warning. Confidence: 75%